Risk factors associated with multi-drug-resistant Acinetobacter baumannii nosocomial infections at a tertiary care hospital in Makkah, Saudi Arabia - a matched case–control study - Al-Gethamy, Manal M (J Int Med Res, 2017)
OBJECTIVE: To determine risk factors for multi-drug-resistant Acinetobacter baumannii (MDR-AB) nosocomial infections in intensive care units in a tertiary care hospital, Makkah, Saudi Arabia. METHODS: We performed a hospital-based, matched case–control study in patients who were admitted to Al Noor Specialist Hospital between 1 January 2012 and 31 August 2012. The study included cases of A. baumannii nosocomial infection and controls without infection. Controls were matched to cases by age and ward of admission. RESULTS: The most frequent site of infection was the respiratory tract (77.3%). Susceptibility to antimicrobial MDR-AB was 92.0% for ceftazidime and ciprofloxacin, while it was 83.3% for imipenem, 83.0% for trimethoprim, 79.0% for amikacin, and 72.7% for gentamicin. Multiple logistic regression of risk factors showed that immunosuppression (OR = 2.9; 95% CI 1.5–5.6; p = 0.002), clinical outcome (OR = 0.4; 95% CI 0.3–0.9; p = 0.01), invasive procedures (OR = 7.9; 95% CI 1.8–34.2; p = 0.002), a central venous catheter (OR = 2.9; 95% CI 1.5–5.6; p = 0.000), and an endotracheal tube (OR = 3.4; 95% CI 1.6–7.3; p = 0.001) were associated with MDR-AB. CONCLUSIONS: Acinetobacter nosocomial infections are associated with admission to the ICU (Intensive care unit) and exposure to invasive procedures.